From Classical Liberalism to Neoliberalism: Explaining the Contradictions in the International Environmental Law Project - Mayrand, Hélène (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2020)
This paper provides a critique of the development of international environmental law, showing the influence of ideologies of classical liberalism, welfarist liberalism and neoliberalism on key legal texts. Sharing the assumptions of critical approaches to law and applying a methodology in line with ideology critique, this paper is aimed at deconstructing the prevailing Western understanding of the positive evolution of international environmental law towards better environmental protection. First, it describes the classical liberal understanding of nature and concepts to address environmental problems before World War II through the example of fisheries agreements. Second, it moves to the influence of welfarist liberalism on international law following World War II, which gave rise to several environmental instruments, especially marine pollution agreements, and later the Stockholm Declaration. Third, it looks at the conceptual shift under the influence of neoliberalism that occurred in the 1990s in the Rio Declaration as well as in the biological diversity and climate change regimes. As the paper shows, instead of changing the problematic understandings of nature in international law, international environmental law relies on these liberal classical understandings and further exacerbates the instrumentalization of nature with the focus on economic rationality, and favouring cost-benefit analysis, deformalization of law, deregulation and self-regulation by private actors, management by experts, and market mechanisms to address environmental problems.